Optical Approaches to Capture Plant Dynamics in Time, Space, and Across Scales - Alexander Bucksch (Frontiers Research Topics, 2018)
Quantifying temporal changes in plant geometry as a result of genetic, developmental, or environmental causes is essential to improve our understanding of the structure and function relationships in plants. Over the last decades, optical imaging and remote sensing developed fundamental working tools to monitor and quantify our environment and plants in particular. Increased efficiency of methods lowered the barrier to compare, integrate, and interpret the optically obtained plant data across larger spatial scales and across scales of biological organization. In particular, acquisition speed at high resolutions reached levels that allow capturing the temporal dynamics in plants in three dimensions along with multi-spectral information beyond human visual senses. These advanced imaging capabilities have proven to be essential to detect and focus on analyzing temporal dynamics of plant geometries. The focus of this Research Topic is on optical techniques developed to study geometrical changes at the plant level detected within the wavelength spectrum between near-UV to near infrared. Such techniques typically involve photogrammetric, LiDAR, or imaging spectroscopy approaches but are not exclusively restricted to these. Instruments operating within this range of wavelengths allow capturing a wide range of temporal scales ranging from sub-second to seasonal changes that result from plant development, environmental effects like wind and heat, or genetically controlled adaption to environmental conditions. The Research Topic covered a plethora of methodological approaches as suggestions for best practices in the light of a particular research question and to a wider view to different research disciplines and how they utilize their state-of-the-art techniques in demonstrating potential use cases across different scales.